Ergonomic hazards associated with Steel Manufacturing Industry: the case of a steel making company in Redcliff, Zimbabwe - Mamvura, Tendai; Jerie, Steven (Midlands State University, 2019)
The aim of this study was to examine the ergonomic hazards that are associated with steel manufacturing at a plant in Redcliff, Harare. The objectives of the study were to identify the ergonomic hazards, analysis of their effects and an assessment of the effectiveness of measures that are in place to combat the impacts of the hazards on employees. The research encompassed both qualitative and quantitative research paradigms and the use of primary and secondary methods of collecting data pertaining to ergonomic hazards associated with steel manufacturing. Primary data was gathered through questionnaires, field observations and interviews while secondary data was obtained from the company health and safety records, clinic records, national health and safety policies and journals. Results from the study indicated that the level of knowledge and appreciation of ergonomics amongst the employees was still low due to inadequate training and lack of management commitment. There is need to consider ergonomic interventions in the day to day operations of the company in order to reduce work related ergonomic hazards, risk factors and ergonomic injuries.